ANALISIS UNDANG-UNDANG NOMOR 28 TAHUN 2004 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 16 TAHUN 2001 TENTANG YAYASAN DAN UNDANG – UNDANG PERSEROAN TERBATAS NOMOR 40 TAHUN 2007 TERKAIT KASUS PERSETERUAN ANTARA KPAI DAN PT JARUM INDONESIA - Indrawan Indra; Haryati Haryati (PROGRAM STUDI ILMU KOMUNIKASI, 2020)
PT is a business entity as a legal entity, PT is also a form of business entity. PT becomes a vehicle for people to carry out business activities and seek profits. PT has become the preferred business entity from various groups, from small businesses to conglomerates, from individuals to the Republic of Indonesia for various business activities, from small business services to banking. The diversity of voters and business activities of PT is a challenge for legislation. Likewise with the Foundation Law on some of the substance of the Law on the Foundation in the community there are still various interpretations that can lead to uncertainty and disorder of the law. But the point is that the two regulations that govern have different functions and positions, so it must be clearer and more comprehensive in how to see them, especially regarding a case